Rescue - Watts, Claire (London ; New York : DK, 2001)
Describes rescue techniques and technology used for a variety of disasters, both man-made and natural. Documents rescues from real incidents throughout history and up to the present time.
"A Dorling Kindersley book.".
Includes index.
7.5
5-8
Keywords: Rescue work -- Juvenile literature; Rescue work; Rescue work; Rescue work